The Role of Technology in ESL Instruction: Exploring the Impact of Technology on ESL Instruction (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Technology's influence on ESL classrooms is explored in depth. Make use of today's innovativedigital resources to learn a language in or out of the classroom. Further detail is provided on howtechnology has been utilized to enhance the teaching and learning of language skills. The study's mostimportant finding is that the vast majority of EFL teachers believe that technology may help them enhancetheir teaching and their student's learning. The essay delves into both the benefits and drawbacks ofusing technology in ESL lessons. The essay finishes with numerous recommendations for enhancingthe instruction of English to those for whom it is a second language.